The variable role of SIRT1 in the maintenance and differentiation of mesenchymal stem cells. (1st May 2018) - Zainabadi, Kayvan
SIRT1 is an NAD + -dependent deacetylase that acts as a nutrient sensitive regulator of longevity. SIRT1 also acts as a key regulator of mesenchymal stem cells (MSCs),  adult stem cells that give rise to tissues such as bone, fat, muscle and cartilage. This review focuses on how SIRT1 regulates the self-renewal, multipotency and differentiation of MSCs. The variable role of SIRT1 in promoting the differentiation of MSCs towards certain lineages, while repressing others, will be examined within the broader context of aging,  calorie restriction, and regenerative medicine. Finally, recent animal and human studies will be highlighted which paint an overall salutary role for SIRT1 in protecting MSCs (and resulting tissues) from age-related atrophy and dysfunction.